A RARE PRESENTATION OF SYNOVIAL SARCOMA - Iqbal, Sana; Kashif, Mehwash (Journal of Ayub Medical College Abbottabad, 2022)
A 36 years old male, presented to the Department of Oral and Maxillofacial Surgery of Abbasi Shaheed Hospital, Karachi, Pakistan, on 7th February 2020 with the complaint of swelling on the left side of the face for more than 1 year. The swelling was 7 x 7 cm in size, intact and palpable, starting from the Zygomatic arch and extending to the lower border of the mandible. The swelling was firm, non-tender, non-fluctuant, non-pulsatile, well localized, well-defined margin, and overlying skin appear normal, with any other complaint of pain, burning sensation, or paresthesia. The intraoral examination revealed occlusion intact, poor oral hygiene, dentate, normal oral mucosa with non-significant bony contour. Mouth opening 40 mm. No deviation of the mandible on opening and closing.